Constructing Elementary School Students Moral Actions Through Global Citizenship Education - Daryati; Triyanto; Deni Zein Tarsidi (South Sulawesi Education Development (SSED), 2026)
In an era of globalization, elementary school students are often exposed to diverse values that can cloud their moral.The crisis of moral degradation among the younger generation demands a reorientation of learning that focuses not only on cognitive intelligence but also on character development aligned with universal human values.This study aims to explore the process of constructing moral actions of elementary school students within the framework of Global Citizenship Education (GCE). Amidst the challenges of ethical degradation in the digital era, GCE is present as an instrument to expand children's moral understanding from a local to a universal scale. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, participatory observation, and documentation studies on students and teachers at the elementary school level. Data analysis was carried out interactively to determine the phenomenon of students' moral development. The results of the study revealed that the construction of students' moral actions is formed through three transformative stages, namely (1) the Cognitive Stage, namely the formation of knowledge and understanding of global issues that provide an objective understanding of humanitarian and environmental issues, (2) the Moral Movement Stage, namely the affective internalization process where knowledge turns into empathy and deep concern and (3) the Action Movement Stage, namely the manifestation of real behavior in everyday life such as environmental care practices, honesty, and social solidarity. These findings confirm that elementary school students' moral actions are not formed instantly, but rather the result of the construction of global knowledge that touches the emotional side of children. This confirms that when global citizenship values are effectively integrated, individuals tend to demonstrate moral behavior that becomes a more consistent habit, both locally and internationally. This study concludes that strengthening moral action is an essential outcome of the Community Service Program (PKG), which can transform students from mere global observers into active moral actors.